On the periodic logistic equation - Al-Sharawi, Ziyad (2006)
We show that the -periodic logistic equation ₙ₊₁ = μₙ mod ₙ(1 - ₙ) has cycles (periodic solutions) of minimal periods 1; ; 2; 3; …. Then we extend Singer’s theorem to periodic difference equations, and use it to show the -periodic logistic equation has at most stable cycles. Also, we present computational methods investigating the stable cycles in case = 2 and 3.